SUSTAINABLE FOREST MANAGEMENT IN LOWER KINABATANGAN, SABAH: ISSUES AND CURRENT PRACTICES - Abdul Latip, Normah; Badarulzaman, Nurwati; Marzuki, Azizan; Umar, Mohd Umzarulazijo (PLANNING MALAYSIA, 2013)
Since 1992, when the first United Nations’ Earth Summit was held in Rio de Janeiro, sustainable forest management (SFM) has been increasingly used to maintain a balance between social, economic and environmental development. In line with this, the successful implementation of SFM depends in large measure on the involvement of all the stakeholders. However, in the Lower Kinabatangan area, not all the stakeholders, especially the local community, are involved in the decision making process when it comes to forest management. The primary objective of this research is to explore the views of the three major stakeholders (Government, Private Sector and Local Community) with regard to issues concerning the environment, the current methods of forest management and the factors that are having an impact on SFM in Lower Kinabatangan. The quantitative method was used in this research and the data was obtained through questionnaires which were distributed to a stratified sample of the target population of stakeholders. Of the 160 questionnaires that were distributed, 115 or 56% of them were returned. The data analysis revealed some similarities and differences in the viewpoints of the stakeholders. It was found from this research that the majority of the respondents were in favour of improving forest management as a way to solve the environmental issues that have arisen in Lower Kinabatangan.